Highly‐selective, closely‐spaced, dual‐band FSS with second‐order characteristic. Issue 10 (1st July 2016) - Yan, Mingbao; Wang, Jiafu; Qu, Shaobo; Feng, Mingde; Li, Zhiqiang; Chen, Hongya; Zhang, Jieqiu; Zheng, Lin
Abstract : In this study, a closely‐spaced, dual‐band, band‐pass frequency selective surface (FSS) is presented by cascading a two‐layer periodic array. The proposed FSS provides two compact pass‐bands separated by two transmission zeros, leading to highly selective response. Each pass‐band contains two transmission poles, which results in a broad band performance. In addition, the FSS has wide out‐of‐band rejection due to that the other two transmission zeros occur at upper side of the higher pass‐band. The simulation is implemented using full wave electromagnetic wave simulator CST Microwave Studio. The proposed FSS structure is fabricated and measured. Both measured and simulated results show that the operating frequencies of the two pass‐bands are, respectively, centred at 9.25 and 11.3 GHz, which are very close to each other. Furthermore, the FSS has the merits of polarisation insensitivity and incident angle stability.